Muslim Fashion Center in Pekanbaru with a Futuristic Architecture Approach - annisa rosyadi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2020)
AbstractThe development of the modern era now makes fashion a reflection of developments in people's lives. As a country that has the largest Muslim majority population in the world. Indonesia has a great opportunity to become one of the world's fashion centers, especially for Muslim fashion. Pekanbaru is a developing city especially in fashion. Along with the needs of Muslim malays, Muslim societies make Muslim clothing a part of the main fashion items. The Muslim Fashion Center was designed because of the lack of a forum for producers and enthusiasts about Muslim fashion in Pekanbaru and a container that can accommodate as an interaction space for information, commercial, recreational and educational activities. In this design using a dynamic futuristic architecture, always changing according to the wishes and times. This application is in accordance with fashion that always develops from time to time. One characteristic of futuristic architecture is nihilism which forces the design of space, so the design is plain, simple and the use of wide glass. Similarly, Muslim fashion tends to be simple and loose (not tight) or wide.